Hubungan Prestasi Kerja Perawat dengan Kepuasan Pasien - Lina Rizki; Mula Tarigan; R Kintoko Rochadi (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between nurse performance and patient satisfaction at RSU. Royal Prima Medan. This research method is correlation research with a quantitative approach. The sample of this study was inpatients, namely as many as 99 respondents using a convenience sampling technique. Data collection using a questionnaire. Data analysis used Spearman rank statistical test analysis. The results showed that there was a relationship between nurse performance and patient satisfaction p = 0.000 (p <0.05). Based on Spearman's rank correlation coefficient for nurse performance with patient satisfaction obtained by 0.525 means there is a moderate and unidirectional relationship between the two variables. The better the nurse's work performance, the patient's satisfaction will also increase. In conclusion, there is a relationship between nurse performance and patient satisfaction at RSU. Royal Prima Medan. Keywords : Job Performance, Nurse, Patient Satisfaction.